Performance of Annona Plants Subjected to Different Graft Combinations, Soil Types and Iron Fertilization - May Hammoud; Zeina El Sebaaly; Saleh Mobarak Alturki; Salim Kattar; Youssef Najib Sassine (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
In the last decade, annona crop was introduced to Lebanon. This experiment was conducted to enhance the adaptation of annona to local conditions. Three scion/rootstock combinations were obtained from self– and cross– cleft grafting of Annona squamosa (Sq) and Annona cherimola (Ch), planted in calcareous “white soil” and clay–loamy “red soil”, and fertilized or not by iron (Fe) through fertigation. In the third year, the treatment red soil–iron fertilization–Sq/Ch had significantly highest plant height, trunk diameter, leaf number, number of primary roots, fruit number and yield. In the third year, despite iron fertilization, plants of the three graft combinations cultivated in red soil had higher flower number, fruit number, individual fruits weight and yield, than those planted in white soil. In the same year, iron fertilization in white soil had only affected total dry mass, leaf mass fraction and leaf iron content. However, iron fertilization of Sq/Ch planted in red soil has improved leaf number, primary root number, primary root length, leaf chlorophyll index, and leaf iron content compared to non–fertilized plants. Conclusively, iron fertilization in red soil could be a useful method improving the performance and yielding capacity of annona crop mainly in Sq/Ch combination.